HISTOLOGICAL AND MICROBIOLOGICAL RATIONALE FOR THE USE OF MATRIX MATERIALS IMPREGNATED WITH ANTIBIOTICS FOR THE RECONSTRUCTION OF BONE TISSUE DEFECTS - Pantus, A.V.; Rozhko, M.M.; Piuryk, V.P.; Paliychuk, I.V.; Kovalchuk, N.Ye.; Divnych, T.Ya. (World of Medicine and Biology, 2024)
Studying the combination of fibrous scaffold materials with therapeutic agents as a drug delivery system is important for regenerative medicine. The results of the antibiotic-absorbing capacity of the fibrous non-woven polycaprolactone matrices created by us, as well as their influence on the regeneration of bone tissue, were analyzed in the study. The results of microbiological studies indicated the pronounced hydrophilic properties of the matrices we’ve created; it was confirmed by a decrease in the activity of the antibiotic only at 16.4 % after 7 days (р
Keywords: matrix materials; polycaprolactone; antibiotic impregnation; cefazolin; lincomycin; histological analysis; bone tissue